High‐resolution genotyping of HLA class I loci in children with type 1 diabetes and celiac disease. (4th May 2021) - Alshiekh, Shehab; Geraghty, Daniel E.; Agardh, Daniel
Abstract : Objectives: HLA‐DQ2 and DQ8 contribute to the strongest risk haplotypes for type 1 diabetes (T1D) and celiac disease (CD). The variation in genetic risk association is likely linked to different HLA class II loci susceptibility, but association studies of HLA class I alleles are scarce. The aim was to investigate HLA class I A, B, and C alleles polymorphisms in children with only T1D, CD, and a subgroup with both T1D and CD (T1D w/CD). Materials and methods: HLA class I A, B, and C genes were genotyped using next‐generation targeted sequencing. A conditional analysis was performed on 68 children with T1D, 219 children with CD and seven children with T1D w/CD enrolled from a birth cohort study at high genetic risk children from the South of Sweden. Results: Among 1764 HLA class I allele variants, A*29 : 02 : 01 in T1D w/CD was associated with both T1D (OR = 21.42 [1.05, 1322.4], p  = 0.0231) and CD (OR = 35 [2.36, 529.12], p  = 0.0051) along with C*05 : 01 : 01 with both T1D (OR = 5.54 [1.06, 24.8], p  = 0.02) and CD (OR = 6.84 [1.46, 26.01], p  = 0.0077). No independent effects of HLA‐B allele associations were observed in T1D w/CD. Conclusion: Although the distribution of HLA class I alleles differs between children with T1D and CD, the A*29 : 02 : 01 and C*05 : 01 : 01 alleles showed shared risk association of both diseases.